"When Leo [Lewis] ran dramatics ...," n.d. - Munro, Melville S. (Tufts Archival Research Center, 2005)
Full caption reads: "When Leo ran dramatics, he got right up on the job where he called players to task for their failings and gave prasie where it warranted." 8 x 6, mounted on 8 x 10 in: M. S. Munro, Miscellaneous pictures through the years, Vol. 1, p. 34